2017
DOI: 10.1037/cou0000184
|View full text |Cite
|
Sign up to set email alerts
|

Victimization and depressive symptomology in transgender adults: The mediating role of avoidant coping.

Abstract: Victimization and depressive distress symptoms represent serious and interconnected public health problems facing transgender communities. Avoidant coping is hypothesized to temporarily alleviate the stress of victimization, but has potential long-term mental and behavioral health costs, such as increasing the probability of depressive symptoms. A community sample of 412 transgender adults (M age = 32.7, SD = 12.8) completed a one-time survey capturing multiple forms of victimization (i.e., everyday discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 89 publications
6
64
0
2
Order By: Relevance
“…We found that depression in our participants was significantly predicted by using less problem-focusing and seeking less social support as coping methods and high reliance on avoidance coping. The findings were in line with the same patterns found in recent studies that examined the influence of coping strategies on depression outcomes among LGBT populations in the United States (Toomey, Ryan, Diaz, & Russell, 2018;White Hughto, Pachankis, Willie, & Reisner, 2017). Chronic disease was the last non-minority stress factor associated with depression in LGBT participants.…”
Section: Most Thaisupporting
confidence: 90%
“…We found that depression in our participants was significantly predicted by using less problem-focusing and seeking less social support as coping methods and high reliance on avoidance coping. The findings were in line with the same patterns found in recent studies that examined the influence of coping strategies on depression outcomes among LGBT populations in the United States (Toomey, Ryan, Diaz, & Russell, 2018;White Hughto, Pachankis, Willie, & Reisner, 2017). Chronic disease was the last non-minority stress factor associated with depression in LGBT participants.…”
Section: Most Thaisupporting
confidence: 90%
“…For instance, a study examining anxiety and depression symptoms among TGD individuals found no significant associations with facilitative coping, but avoidant coping strategies were a mediator of the association between TGD identity development and overall distress (Budge et al, ). White Hughto, Pachankis, Willie, and Reisner () also examined avoidant coping and found this type of coping mediated the association between victimization (conceptualized as discrimination, violence, and assault) and depressive symptoms among TGD individuals. Support for the role of approach‐oriented coping strategies is more limited.…”
Section: Coping With Discriminationmentioning
confidence: 99%
“…Minority stress theory suggests that victimisation experiences may contribute to the elevated rates of mental health problems in transgender individuals (Hendricks & Testa, 2012), although the limited evidence from cross-sectional studies is conflicted regarding an association between transphobic victimisation and mental health symptoms (e.g. Bouman, Davey, Meyer, Witcomb, & Arcelus, 2016;White Hughto, Pachankis, Willie, & Reisner, 2017).…”
Section: Introductionmentioning
confidence: 99%